Optimalisasi Komposisi Kandungan MN Pada Filler untuk Mendapatkan Ketangguhan dan Kekerasan - Nur Subeki (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Submerged Arc Welding (SAW) is a welding process used for fabrication of pipes, for example spiral welded pipes. The technique can be operated automatically and has a high reliability in many various welding applications. Some factors affecting the strength of weld metals are heat input, current, and chemical composition of filler, flux, and base metal. The present investigation aims to study microstructure-hardness relationship of submerged arc spiral welded steel pipes. Material used in this experiment was API 5L X-52 and API 5L X-60 for spiral welded steel pipes. Welding was carried out using voltage of 35 volt, welding speed of 13,67 mm/s whereas composition Mn on the flux was varied, 1.7; 1.4; 1.4 with Mo and 1.09. Microstructure and hardness were conducted on base metal, weld metal and heat affected zone (HAZ). Results show that, an increase in composition of Mn could be increases the amount of acicular ferrite structure in weld metal. The hardness and thougness number is increase correlated with increase number of Mn, but for the composition Mn as 1,7, the number of acicular ferrite is decrease, the consequence of hardness number is decrease.